Analisis Wacana Kritis Berita Kriminal PADA RAKYAT BENGKULU.COM (Studi Berita Kriminal Oknum Polisi Cabuli Remaja Putri) - Lupita, Rena; Sari, Sapta; Yanto, Yanto (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
News is the latest information or information about something that is happening. News is usually presented through print, broadcast, internet or by word of mouth to third parties and the general public. This research aims to find out and analyze the critical discourse of kriminal news on Rakyat Bengkulu.Com (Study of Kriminal News by Police Officers Cabuli Young Women), this research is qualitative research. The results of this research show a critical discourse analysis of kriminal news on Rakyat Bengkulu.Com (Study of Kriminal News by Police Officers Obscuring Young Women) that in the analysis of the kriminal news text on Rakyat Bengkulu.Com, it can be seen that the text reflects a case of alleged immoral acts involving a police officer and a woman. From this analysis, it was found that the news described the case situation, chronology of events, investigation steps, and the victim's request for accountability. Furthermore, in discursive (mesostructural) analysis, it is shown that the mass media has ideological considerations and journalists' work routines in determining how news is presented. In the context of the Rakyat Bengkulu.Com news, this discursive aspect includes the production, dissemination and consumption of news which influences readers' understanding and reactions to the case. Finally, in socio-cultural (macrostructural) analysis, it was found that this case had situational, institutional and social dimensions that influenced various aspects of the victim's life, the responsibilities of the police institution and broader social issues. This shows the role of the media in shaping opinions and responding to relevant social and legal issues.